Comprehensive Management of Electricity Demand Distribution in Time - Serebrennikov B.; Petrova K.; Serebrennikov S. (Problems of the Regional Energetics, 2023)
The paper is aimed to strengthen the controllability of electricity consumption mode at all structural layers of the country’s energy system (ES) to establish the optimal load curve in the PS. Following this goal, the energy system was broken down into seven structural layers - from the technological operation to the ES. For each layer, an expert assessment of the effectiveness of six institutional and operational methods of electricity demand-side management (DSM) was done. The integrated application of the suggested methods was tested in two industrial consumers, which proved the effectiveness of this approach for leveling their aggregated load curve. To ensure an appropriate economic impact on the electricity demand, given the influence of individual consumers on the load curve fluctuation in the ES, a particular price function considering the cross-correlation coefficient of the load curves was developed. It was proved that the complex DSM methods application significantly improved the controllability of the electricity consumption mode. To incentivize consumers to adjust their electricity consumption, a special price system functionally related to the cross-correlation coefficient of the consumer and the ES load curves was developed. The marginal price values depending on the cross-correlation coefficient were defined, while the intermediate price values were calculated by the functional transformation of the ES load curve into the price scale. The significance of the research results lies in the fact that ranking the DSM methods by the priority of application for various structural layers of ES and their integrated application almost doubled the DSM effectiveness.